Multimodality, creativity and children’s meaning-making: Drawings, writings, imaginings - Bock, Zannie (Stellenbosch Papers in Linguistics Plus, 2016)
This paper uses a case study of the drawings, early writings and imaginative role play of two children to illustrate how children use a variety of modes to make meaning in ways that are creative and beyond the design and expectation of adults. It aims to valorise the kinds of practices in which children routinely engage but which are often overlooked and de-valued by adults, both parents and teachers. Framed by social semiotic theories of communication, multimodal pedagogies and cognitive accounts of children’s drawings, it illustrates how the children in this study work easily and seamlessly across a variety of materials and modes, using the semiotic resources available in their environments, to create imaginary worlds and express meanings according to their interests. In profiling these children, this paper lends support to the claim of multimodal pedagogies that it is the shifting across modes, as well as the freedom to choose the mode of expression, that engages the child’s affect and creativity and builds agency and voice.